The Influence of Celebrity Endorsers, Attitude Towards the Brand Through Brand Image on Customer Purchasing Decisions on Glico Wings Ice Cream - Christianto, Maresky; Tyas, Ari Anggarani Winadi Prasetyoning (International Journal of Economics (IJEC), 2024)
This study aims to examine the influence of Celebrity Endorser, Attitude Toward The Brand through Brand Image on Customer Purchase Decisions on Glico Wings ice cream. This research is motivated by an increase in purchase decisions due to promotions from celebrity endorsers, thus creating an Attitude Toward Brand from consumers and finally creating a good Brand Image. This study used respondents with the criteria of having Instagram social media accounts and having bought and tasted Glico Wings ice cream in the Tangerang area. The sampling technique used in this study used a purposive sampling technique of 170 respondents using the SEM analysis method. The results of the research in this study show that Celebrity Endorser and Attitude Toward The Brand have a positive effect on Brand Image, Celebrity Endorser and Attitude Toward The Brand also have a positive effect on Purchase Decisions, but Brand Image has no effect on Purchase Decisions. Then Brand Image mediates Celebrity Endorser also has no effect on purchase decisions and also Brand Image mediates Attitude Toward The Brand also has no effect on purchasing decisions. Managerial implications for Glico Wings ice cream in order to be able to improve marketing strategies by using various platforms, content and features that are in accordance with the characteristics and preferences of their Celebrity Endorsers for the target market they are targeting and can provide superiority in their products and carry out brand awareness through social media ads and Google ads.